2021
DOI: 10.3389/fendo.2021.751213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Microwave Ablation in the Treatment of Low-Risk Papillary Thyroid Microcarcinomas and Related Histopathological Changes

Abstract: ObjectiveThis study aimed to evaluate the feasibility and efficacy of ultrasound-guided percutaneous microwave ablation (MWA) in the treatment of low-risk papillary thyroid microcarcinoma (PTMC), and to observe the histopathological changes after MWA.MethodsMWA was performed under ultrasound guidance for 73 unifocal PTMC patients without clinically cervical or distant metastasis. The target ablation zone exceeded the tumor edge (judged by contrast-enhanced US) to avoid marginal residue and recurrence. Ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Lu et al. ( 15 ) also reported that no characteristics of PTC were found by FNA and CNB at the 3 months and 6 months follow-up in 44 patients with unifocal micro-PTC who underwent MWA. In other studies, the local recurrence rate after MWA treatment was also very low ( 16 18 ).…”
Section: Discussionmentioning
confidence: 97%
“…Lu et al. ( 15 ) also reported that no characteristics of PTC were found by FNA and CNB at the 3 months and 6 months follow-up in 44 patients with unifocal micro-PTC who underwent MWA. In other studies, the local recurrence rate after MWA treatment was also very low ( 16 18 ).…”
Section: Discussionmentioning
confidence: 97%
“…MWA is another novel tumor ablation technology which developed from biologic thermal effects, which is mainly applied in the treatment of solid tumors in liver ( 40 ), lung ( 41 ), kidney ( 42 ), adrenal gland ( 43 ), spleen ( 44 ), thyroid ( 45 ) and breast ( 46 ). The therapeutic effects of MWA depends on the dipolar molecules (primarily water) to align and realign according to the variable electromagnetic field.…”
Section: The Principle Of the Ablation Techniquesmentioning
confidence: 99%
“…Coagulative necrosis often occurs in the central area, leading to the release of new antigens in tumor cells, which is called tumor in situ vaccination, while the transition zone is easily affected by residual temperature, resulting in secondary effects such as immune activation (17). However, the latest research shows that thermal ablation not only irreversibly denatures the newly released antigens in the central area of tumor tissues but may also upregulate some carcinogenic factors (such as interleukin-6(IL-6) and vascular endothelial growth factor(VEGF)), aggravating the progression of tumor metastasis (18,19). However, thermal ablation still has some positive immunomodulatory effects, such as the release of positive immunomodulatory factors, initiation of a local inflammatory response, and recruitment of immune cells (18,20).…”
Section: Effects Of Thermal Ablation and Mild Hyperthermia On The Imm...mentioning
confidence: 99%
“…However, the latest research shows that thermal ablation not only irreversibly denatures the newly released antigens in the central area of tumor tissues but may also upregulate some carcinogenic factors (such as interleukin-6(IL-6) and vascular endothelial growth factor(VEGF)), aggravating the progression of tumor metastasis (18,19). However, thermal ablation still has some positive immunomodulatory effects, such as the release of positive immunomodulatory factors, initiation of a local inflammatory response, and recruitment of immune cells (18,20). Compared with thermal ablation, the main effect of mild hyperthermia is not necrosis, but apoptosis, vascular permeability, and immune effect.…”
Section: Effects Of Thermal Ablation and Mild Hyperthermia On The Imm...mentioning
confidence: 99%